2022
DOI: 10.4054/demres.2022.47.12
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Swedish fertility decline of the 2010s

Abstract: BACKGROUNDThe downward fertility trend in Western countries during the 2010s is puzzling, not least in the Nordic region. OBJECTIVEIn order to better understand its driving forces, we examine whether the decline is driven by differential behavior or compositional changes across sociodemographic population subgroups, for the empirical case of Sweden. METHODSEvent-history techniques are applied to register data of the Swedish-born population to provide an in-depth analysis of the sociodemographic profile of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
5
17
0
Order By: Relevance
“…Previous research has described pronounced and rather similar declines in the 2010s across population sub-groups, which has made it difficult to identify the underlying drivers. Still, by now one feature stands out; the decline in first births has accelerated among the least educated (Comolli et al 2020) in all Nordic countries, and at least in Sweden, among those with weaker labour market attachment and lower earnings (Ohlsson Wijk and Andersson 2022). The findings of this study are in line with these previously observed patterns but highlight that first births are being increasingly postponed or foregone not only among those without a degree but also by those with a degree but educated in fields characterized by higher economic uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has described pronounced and rather similar declines in the 2010s across population sub-groups, which has made it difficult to identify the underlying drivers. Still, by now one feature stands out; the decline in first births has accelerated among the least educated (Comolli et al 2020) in all Nordic countries, and at least in Sweden, among those with weaker labour market attachment and lower earnings (Ohlsson Wijk and Andersson 2022). The findings of this study are in line with these previously observed patterns but highlight that first births are being increasingly postponed or foregone not only among those without a degree but also by those with a degree but educated in fields characterized by higher economic uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…The Nordic fertility decline appears to be a relatively universal phenomenon; beyond the much faster reduction in first births among childless women than in subsequent childbearing among mothers (Hellstrand et al 2021), previous studies have not found large variation across other population subgroups, e.g. by sub-national region, educational level, or migration background (Campisi et al 2020;Ohlsson Wijk and Andersson 2022). However, the first birth decline has been somewhat more pronounced among the lower educated (Comolli et al 2020;Hellstrand, Nisén, and Myrskylä 2022) and those with a weaker labour market attachment (Ohlsson Wijk and Andersson 2022).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Nordic fertility decline appears to be a relatively universal phenomenon; beyond the much faster reduction in first births among childless women than in subsequent childbearing among mothers (Hellstrand et al 2021), previous studies have not found large variation across other population subgroups, e.g. by sub-national region, educational level, or migration background (Campisi et al 2020;Ohlsson Wijk and Andersson 2022). However, the first birth decline has been somewhat more pronounced among the lower educated (Comolli et al 2020;Hellstrand, Nisén, and Myrskylä 2022) and those with a weaker labour market attachment (Ohlsson Wijk and Andersson 2022).…”
Section: Introductionmentioning
confidence: 89%
“…by sub-national region, educational level, or migration background (Campisi et al 2020;Ohlsson Wijk and Andersson 2022). However, the first birth decline has been somewhat more pronounced among the lower educated (Comolli et al 2020;Hellstrand, Nisén, and Myrskylä 2022) and those with a weaker labour market attachment (Ohlsson Wijk and Andersson 2022).…”
Section: Introductionmentioning
confidence: 97%